Análisis preliminar en procesos de almidón termoplástico para la generación de bioplástico a partir de tres semillas aguacate, mango y tamarindo (2021)
In this paper we analyze different biologic-based raw materials for the production of bioplastic from starch processes, for it is bace use of different technical and practical studies where the process of thermoplastic starch is highlighted, for its ease and effectiveness at the time of generating highly biodegradable bioplastic resins. A cancerization of avocado, mango and tamarind seeds is carried out, highlighting their percentage of starch over the rest of the properties, in order to determine which of the different vaniities of the aforementioned seeds are the best, to generate bioplastic from thermoplastic starch processes.